Unlocking the Potential: The Impact of E-SPT and E-Filing Systems on Boosting Corporate Tax Revenue - Oktaviano, Benny; Sulistyorini Wulandari, Dian; Boru Tarigan, Nora Vira Yunika (PT. Banjarese Pacific Indonesia, 2024)
This study uses multiple linear regression analysis as the primary analytical tool to investigate the transformative effects of Electronic Self-Assessment Tax (E-SPT) and E-Filing systems on corporate tax revenue. By examining the integration of these digital tools, the research highlights their significant impact on enhancing tax administration efficiency, accuracy, and compliance. E-SPT simplifies the tax reporting process, reduces administrative burdens, and minimizes errors through automated checks. E-Filing improves transparency and accountability by providing clear, traceable records of submissions. Together, these systems streamline tax compliance, increase taxpayer awareness, and boost overall revenue collection. The study is based on a sample of 100 corporate taxpayers registered at KPP Pratama. The findings indicate that the adoption of E-SPT and E-Filing systems results in significant improvements in corporate tax revenue, emphasizing the role of digital solutions in modernizing tax systems.